Understanding Intimate Partner Violence Perpetration Involving the Deaf Population - Mastrocinque, Jeanna M. (Journal of interpersonal violence, 2022)
There has been an increase in intimate partner violence (IPV) research regarding the deaf population; however, no studies to date obtained data directly from members of the deaf population who disclose IPV perpetration. This community-based participatory research study explored the social context of IPV perpetration involving the deaf population through interviews with deaf or hard-of-hearing individuals who self-identified as perpetrating either physical or sexual abuse in an intimate relationship where at least one partner was deaf. Through semi-structured interviews using video relay, an interdisciplinary research team, which included deaf investigators, explored questions which included IPV triggers, types of IPV, weapon use, childhood victimization, and interactions with first responders and response systems (e.g., criminal justice, medical). The types of IPV abuse, resulting injuries, and systems used are discussed. The team collectively identified key elements of abuse and their relationships to each other through concept mapping of each interview. Through a method of constant comparison, we identified several themes: intergenerational transmission of violence, fund of information concerns, communication barriers with family and friends and resulting frustration, and help-seeking challenges. Many of these themes are specific to the deaf population, illustrating the need for continued research to understand IPV in diverse communities. Findings are compared with IPV trends in the general (hearing) population, and prompt concerns that universal IPV interventions may not effectively address the needs of the deaf population. Recommendations for diversifying screening efforts, modifying screening tools, and tailoring interventions to better address IPV involving deaf and hard-of-hearing populations are discussed.